2017
DOI: 10.1039/c7nr01035d
|View full text |Cite
|
Sign up to set email alerts
|

High performance bi-layer atomic switching devices

Abstract: Atomic switches, also known as conductive bridging random access memory devices, are resistive-switching devices that utilize the electrochemical reactions within a solid electrolyte between metal electrodes, and are considered essential components of future information storage and logic building blocks. In spite of their advantages as next generation switching components such as high density, large scalability, and low power consumption, the large deviations in their electrical properties and the instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The extremely high on/off ratio is promising for multilevel switching [31,32] and future neuromorphic computing to ensure the enhance conduction states. Though the device is unable to go for long P/E endurance keeping such a high order on/off ratio, still this result is comparable with recently published works as listed in Table 1 [10,11,[33][34][35][36][37][38]. By reducing pulse width from 500 µs to 1 µs, P/E cycles are improved to 100 P/E cycles, as shown in Figure 7b.…”
Section: Read Endurance and Data Retention Characteristicssupporting
confidence: 85%
See 1 more Smart Citation
“…The extremely high on/off ratio is promising for multilevel switching [31,32] and future neuromorphic computing to ensure the enhance conduction states. Though the device is unable to go for long P/E endurance keeping such a high order on/off ratio, still this result is comparable with recently published works as listed in Table 1 [10,11,[33][34][35][36][37][38]. By reducing pulse width from 500 µs to 1 µs, P/E cycles are improved to 100 P/E cycles, as shown in Figure 7b.…”
Section: Read Endurance and Data Retention Characteristicssupporting
confidence: 85%
“…After formation of the pristine devices, a reduction and oxidation at the neck region will be responsible for LRS and HRS of the devices. For the S2 devices, the high electric filed controls across [11] 7/−9 0.1/10 5/5 10 7 10 5 10 6 Cu/TaO x /Ta 2 O 5-x /Pt [33] -/-0.1/0.1 -3000~10 5 >10 4 at 85 • C Cu/HfO 2 :Cu/Pt [34] -/-1/1 0.01/100 >100 10 7 10 5 Al/CH 3 NH 3 Pbl 3 :PVA m.Hl/ITO/Glass [35] 3/−1 100/100 10 4 /10 4 500 >10 5 10 4 Cu/Ti/PVP-PMF/Pt [36] 1/−0.5 1/5 10 4 /10 4 >10 3 >10 3 >10 3 at 85 • C Ag/HfO x :N/Pt [37] 2/-0.1/-50/50 10 6 5 × 10 8 -Cu/NG/HfO 2 [38] 4/−4 0.5/0.5 0.5/0.5 10 7 >10 6 2 × 10 5 at 125 • C…”
Section: Cbram Mechanismmentioning
confidence: 99%
“…Because the electrode diameter is 50 µm, the switching energy would be 5–7.5 fJ for an individual device if 500 nm technology is adopted. Therefore, our memristor has an advantage in energy consumption because most reported memristors prepared under the technique with line width down to hundreds of nanometers operate on a current level of microampere . Some typical energy consumption data are listed in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al ( 2014 ) reported that the switching mechanisms in memristive devices produce conductive filaments (CFs) in the switching layer (SL). CF-forming mechanisms such as filaments form along with oxygen vacancies (Ju et al 2017 ) and electrode diffusion (Xu et al 2014 ). Other theories have recently been published to elucidate the switching behavior such as field-induced electron hopping transport (Ielmini and Zhang 2007 ) and metastable metavalent bond formation (Noé et al 2020 ; Raty and Noe 2020 ).…”
Section: Introductionmentioning
confidence: 99%